IMPLEMENTASI PENDEKATAN SAINTIFIK PADA PEMBELAJARAN ILMU PENGETAHUAN ALAM DI MIS IKHWANUL MUKMININ - Luthfiyah Zulfaini Silalahi; Alya Putri Dumayanti; Radhiatul Yusra; Nurul Shadrina Husna; Chairunnisa Lubis (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The implementation of a scientific approach is something that needs to be studied more deeply in order to create an active and efficient learning process. This study aims to determine the implementation of learning plans and the application of the scientific approach by science teachers. The method used in this research is a qualitative research method which is also known as naturalistic research. The result of this study is that the science teacher understands the theoretical scientific approach, and is equipped with a plan in the RPP document which is prepared before the lesson takes place. In the process of applying the scientific approach, it takes a longer time to carry out observations, where the media displayed is limited to the use of simple paper, due to the limited supporting learning media such as LCD projectors, and so on.